Weak neck of Musa sp. cv. rastali : a review on it’s genetic, crop nutrition and post harvest - Putra, E. T. S; Wahab , Zakaria; Abdullah, Nur Ashikin Psyquay; Saleh, Ghizan (Asian Network for Scientific Information, 2010)
Weak neck is the physiological weakening at the pedicel of Musa sp. fruit that causes individual fruits to be released prematurely from the hand. The level of resistance to weak neck is different among groups of Musa sp. with A and B genomes, diploid, triploid and tetraploid. Musa sp. cv. Rastali is AAB genome, but this cultivar is sensitive to weak neck. Sensitivity to weak neck comes from the two A genomes. There is high probability that application of Magnesium (Mg), Boron (B) and Silicon (Si) may solve weak neck on Musa sp. cv. Rastali. Magnesium application increases chlorophyll synthesis and photosynthesis rate. Assimilate accumulation on fruit cells triggers cell elongation and cell wall thickening, especially in the neck zone. Boron plays an important role in regulating hormone and enzyme levels in plants. Sufficient boron in plant tissue impedes synthesis and activities of Pectate Lyase (PL) and pectinmethylesterase (PME), thus decreasing cell wall hydrolysis. Plant cells and tissues become stronger with Si application. This is caused by the formation of silica-cuticle double layer on the epidermis. Low temperature along with low relative humidity during storage and ripening decreases the activities of PL and PME. The reduction of PL and PME activities result in a decrease in pectin degradation rate and cell wall hydrolysis, thus reducing the occurrence of weak neck.